Combined role of SiC whiskers and graphene nano-platelets on the microstructure of spark plasma sintered ZrB2 ceramics. Issue 9 (1st May 2021) - Nguyen, Van-Huy; Delbari, Seyed Ali; Shahedi Asl, Mehdi; Le, Quyet Van; Sabahi Namini, Abbas; Ahmadi, Zohre; Farvizi, Mohammad; Mohammadi, Mohsen; Shokouhimehr, Mohammadreza
Abstract: This research explores the sintering behavior and microstructure of ZrB2 -based materials containing graphene nano-platelets (GNPs) and SiC whiskers (SiCw ). Spark plasma sintering (SPS) process at 1900 °C was implemented to sinter the specimen, leading to a composite with 100% relative density. High-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), field emission-electron probe microanalyzer (FE-EPMA), and high-resolution X-ray diffractometry (HRXRD) were employed to study the SPSed sample, along with the thermodynamics predictions. According to the HRXRD result and microstructural observations, the sintering process was non-reactive, which was endorsed with the XPS analysis. Furthermore, graphene presented a beneficial role for eradicating the oxide impurities in the sample during the sintering. Such oxide impurities were reduced to the original phases of SiC and ZrB2, contributing to porosity removal. Nanostructural investigations revealed the formation of ultrathin amorphous interfaces (~10 nm) between ZrB2 /graphene phases, disordered atomic planes in graphene platelets, and dislocations in ZrB2 grains. One reason for generating crystalline defects in the microstructure was found out to be the mismatches amongst the elastic properties of the available compounds in the system.